Korelasi Antara Peraturan Daerah (Perda) Bermasalah Dengan Tingkat Investasi Ke Daerah - Author: Isrok (Jurnal Hukum IUS QUIA IUSTUM, 2009)
Evaluations on local regulation by government and private institutions show that many local regulations are pointed out to be in disagreement with Acts No. 10 of 2004. It impacts public attention on the legislation process for those acts and local regulation. The legislation of those regulations has caused hesitation among local and foreign investors to invest their money there. The lack of investment has a significant impact on the local economy because the Regional Income Rate depends on the investment.Key words: correlation, local regulation, local investment